STUDY OF THE UTILIZATION OF FACILITIES IN TANGKAHAN HORIZON GROUP KOTA SIBOLGA PROVINSI SUMATERA UTARA - Elmayanti Nainggolan; Alit Hindri Yani; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was carried out in February 2019 in Tangkahan Horizon Group, Sibolga City, North Sumatra Province, aiming to determine the level of utilization of existing facilities and find out whether the area has the potential to be developed. Using survey methods, by observing and collecting data directly. The results of calculations from existing facilities indicate that the required pier length is 56.51 meters, and from the results of the analysis of the utilization rate of the pier that is 28.26% which means that the pier is underutilized, while the utilization rate of the port pool is 475.24% which means very exploited. The calculation of the level of utilization of cold storage facilities (Cool storage) then obtained by 93.41%, which means used. The ABF (Air blast frezjer) facility, the utilization rate of ABF (Water blast freezer) is 46.88% which means it is underutilized. Keywords:Utilization of Facilities, Tangkahan Horizon Group, Sibolga City